Increased in vivo perpetuation of whole-heart ventricular arrhythmia in heterozygous Na+/Ca2+ exchanger knockout mice. (February 2023) - Bögeholz, Nils; Knappe, Vincent; Pauls, Paul; Schulte, Jan S.; Goldhaber, Joshua I.; Müller, Frank U.; Nickenig, Georg; Eckardt, Lars; Schrickel, Jan W.; Beiert, Thomas
Abstract: Aims: Na + /Ca 2+ exchanger (NCX) upregulation in cardiac diseases like heart failure promotes as an independent proarrhythmic factor early and delayed afterdepolarizations (EADs/DADs) on the single cell level. Consequently, NCX inhibition protects against EADs and DADs in isolated cardiomyocytes. We here investigate, whether these promising cellular in vitro findings likewise apply to an in vivo setup. Methods/Results: Programmed ventricular stimulation (PVS) and isoproterenol were applied to a murine heterozygous NCX-knockout model (KO) to investigate ventricular arrhythmia initiation and perpetuation compared to wild-type (WT). KO displayed a reduced susceptibility towards isoproterenol-induced premature ventricular complexes. During PVS, initiation of single or double ectopic beats was similar between KO and WT. But strikingly, perpetuation of ventricular tachycardia (VT) was significantly increased in KO (animals with VT - KO: 82 %; WT: 47 %; p = 0.0122 / median number of VTs - KO: 4.5 (1.0, 6.25); WT: 0.0 (0.0, 4.0); p = 0.0039). The median VT duration was prolonged in KO (in s; KO: 0.38 (0.19, 0.96); WT: 0.0 (0.0, 0.60); p = 0.0239). The ventricular refractory period (VRP) was shortened in KO (in ms; KO: 15.1 ± 0.7; WT: 18.7 ± 0.7; p = 0.0013). Conclusions: Not the initiation, but the perpetuation of provoked whole-heart in vivo ventricular arrhythmia was increased in KO. As a potential mechanism, we found a significantly reduced VRP, which may promote perpetuation of reentrant ventricular arrhythmia. On a translational perspective, the antiarrhythmic concept of therapeutic NCX inhibition seems to be ambivalent by protecting from initiating afterdepolarizations but favoring arrhythmia perpetuation in vivo at least in a murine model.